Changes in a secondary forest in southwestern Nigeria following a ground fire - Isichei, Augustine O.; Ekeleme, Friday; Jimoh, Bakare A. (2014)
In January 1983, two 50 m x 50 m rain forest plots in the University of Ife campus in southwestern Nigeria were demarcated for a baseline study of species composition, litterfall and tree girth increments. By accident, a severe ground fire burnt one of the plots on 31 January, barely two weeks after litter traps had been set and species listing and fist girth measurements completed. The effect of this fire was assessed in the burnt plot after 14 months, in April 1984. The fire affected small trees especially, and there were indications that some species were more sensitive than others. Manihot glaziovii, which was present in the plot and abundant in its vicinity before the fire showed a big increase in density after the fire because it was able to germinate in the openings created by the fie. These observations were related to succession, and it is concluded that the observation by some workers that the initial composition of a regrowth forest may be partly predicted from a knowledge of the seed bank in the soil may be applicable in the present case.